PSYCHOLOGICAL PREPARATION OF PATIENTS FOR ANESTHETICS IN MEDICAL PREOPERATIVE SITUATIONS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Surgery has a special place in medicine. There is an opinion among the people that "if the patient cannot be cured by medicines, surgeons will fix it by operation". Compared to therapeutic procedures, surgery is also a great psychological test for most patients and their relatives. Therefore, the importance of psychological support in surgery, as in other areas of medicine, is very high. This article provides information on the psychological preparation of patients for anesthesia in medicine before surgery.